(3GdGYJHGQ aj GdfGSN hGdefShN aj GdMOjKs - (3eMeO Hf ehSi Hf YKeGf GHf MGRe, CHh HcQ, Rjf GdOjf, GdeYQha HGdMGRej,J (B584 (3g` s
(3ChdgG (B:s
(3CeG HYO agPG cJGH CPcQ ajgG eG EfJgJ Edi eYQaJg ef fGSN MOjK QShd Gddg Udi Gddg Ydjg hSde hefShNI s
(3BNQgG (B:s
(3aEP CWjY QShd Gddg Udi Gddg Ydjg hSde abO CWjY Gddg JYGdi HWGYI QShdg Udi Gddg Ydjg hSde BNQ GdLRA GdSGHY hGdMeO ddg hMOg hgh BNQ GdcJGH s
(3HgG fXGe GdJYbjHIs
(3SHYI CLRGA MOjKjIs
(3GdChQGb ef (B10 _ 79 (3HNW eMOK Yf NW GdfSNIs
(3Ydi GdfSNI ELGRI YKeGf Hf eMeO Hf YKeGf GdOjei GdeUQi GdTGaYi dCHi GdMSf Ydi Hf CMeO Hf Ydi GdeUQi GdTGaYi HYO Cf bQC GdcJGH Ydjg SfI (B872 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
Keywords: (3GdMOjK h GdeUWdMs